Strategies Steering Intensification Pathways of Farmers in Central Malawi - Timler, Carl J.; Groot, Jeroen C.J.; Snapp, Sieglinde S.; Tittonell, Pablo Adrian (Springer, 2023)
Smallholder farmers face many challenges to improve their livelihoods and food security. Intensification of agricultural production can help to achieve these goals. Yet farmers are highly heterogenous in their strategies towards intensification, potentially following unsustainable intensification pathways. Using Q Methodology, we ascertain different strategies regarding farm improvement and intensification of smallholder farmers in the Dedza and Ntcheu Extension Planning Areas in Central Malawi. These strategies were associated to coherent sequential choices as expressed in “managerial intensification pathways” (MIPs). Three main strategies emerged: Seed Saving Peasants, Aspirant Modern Farmers and Entrepreneurial Business(wo)men. These were subsequently linked to four MIPs. Seed Saving Peasants focus strongly on local seed systems and post-harvest protection of grains, but also allocate more labour to improving crop residue use and manure quality, thus pointing to a labour-oriented MIP. Aspirant Modern Farmers willingly adopt hybrid seeds and inorganic fertilizers but require more extension support; these farmers follow a technology-oriented MIP. Entrepreneurial Business(wo)men are early adopters of new technologies and benefit from improved access to market information and suppliers of new technologies and follow a sustainable technology-based or techno-ecological intensification pathway. This study shows that strongly contrasting perspectives on intensification exist among smallholders and it is expected that their preferred intensification choices will have diverging impacts on the sustainability of their farms. A diversity of extension, advice and incentive instruments will be needed to support farmer decision making towards sustainably intensified farms.